Humour in Sports Coaching: 'It's a Funny Old Game'. (December 2018) - Edwards, Christian Nicholas; Jones, Robyn L
The primary purpose of this article was to investigate the use and manifestation of humour within sports coaching. This was particularly in light of the social significance of humour as a critical component in cultural creation and negotiation. Data were gathered from a 10-month ethnographic study that tracked the players and coaches of Senghenydd City Football Club (a pseudonym) over the course of a full season. Precise methods of data collection included participant observation, reflective personal field notes, and ethnographic film. The results demonstrated the dominating presence of both 'inclusionary putdowns' and 'disciplinary humour', particularly in relation to how they contributed to the production and maintenance of the social order. Finally, a reflective conclusion discusses the temporal nature of the collective understanding evident among the group at Senghenydd, and its effect on the humour evident. In doing so, the work contributes to the body of knowledge regarding the social role of humour within sports coaching.